2013
DOI: 10.4102/sajcd.v60i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Speech-language therapy for adolescents with written-language difficulties: The South African context

Abstract: Objective: To investigate whether privately practising speech-language therapists in South Africa are fulfilling their role of identification, assessment and intervention for adolescents with written-language and reading difficulties. Further needs concerning training with regard to this population group were also determined.Method: A survey study was conducted, using a self-administered questionnaire. Twenty-two currently practising speech-language therapists who are registered members of the South African Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…However, practitioners who know that an intervention is evidence based do not need to remember a researcher's name in order to carry out intervention appropriately. Consistent with previous findings [23], practitioners were more likely to use experience as a rationale than scientific evidence.…”
Section: What Are the Characteristics Of Practitioners Who Report Using Scientific Evidence When Delivering Intervention?supporting
confidence: 88%
See 2 more Smart Citations
“…However, practitioners who know that an intervention is evidence based do not need to remember a researcher's name in order to carry out intervention appropriately. Consistent with previous findings [23], practitioners were more likely to use experience as a rationale than scientific evidence.…”
Section: What Are the Characteristics Of Practitioners Who Report Using Scientific Evidence When Delivering Intervention?supporting
confidence: 88%
“…The dominance of client-centred responses is positive in practice as personalisation of intervention is important [7]. Previous research has highlighted the need for more individualised interventions [23], and this may have led to client-centred approaches being included in training programmes. Additionally, client-centred characteristics may be dominant as they are driven and promoted in policy guidelines and scope of practice documents emanating from governing bodies and policy makers such as the WHO [37] and CPLOL [38].…”
Section: Do Client Characteristics Affect the Rationales Used For Intervention?mentioning
confidence: 99%
See 1 more Smart Citation
“…The current research findings regarding factual knowledge about SLD (DD) are supported by a previous study conducted in South Africa, pertaining to the knowledge levels of SLTs regarding written language difficulties. According to Erasmus et al (2013), the majority of South African SLTs in private practice acknowledged their role in addressing written language difficulties and felt that they possess the knowledge necessary to do so. Clark, Naidoo and Linenstein (2019), however, reported that South African professionals have limited knowledge about African languages as well as the indicators of SLD (DD) within African languages, as the appearance of these indicators may vary across orthographies.…”
Section: Factual Knowledge About Specific Learning Disorder (Developm...mentioning
confidence: 99%
“…In African countries, research involving professionals practising in SLDs such as SLD (DD) is limited, and a shortage of qualified healthcare professionals, including SLTs, OTs and psychologists, was also identified (Agho & John 2017). Wylie et al (2016) In a study conducted by Erasmus et al (2013), many South African SLTs acknowledged their role in providing assessment and intervention services to individuals affected by language and literacy difficulties. These professionals appeared reluctant, however, in fulfilling their roles relating to written language difficulties, because of low confidence in their abilities and a lack of training.…”
Section: Introductionmentioning
confidence: 99%